1997
DOI: 10.1002/(sici)1097-0010(199706)74:2<229::aid-jsfa793>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Roxarsone on Performance, Toxicity, Tissue Accumulation and Residue of Eggs and Excreta in Laying Hens

Abstract: In this study, we examined the effects of a high dosage of roxarsone in the diet on the performance, liver function, and its residue in liver, eggs and excreta of laying hens. Seventy‐five 32‐week‐old layers were selected and randomly allocated into five dietary treatments with three replications for each treatment. Feeding periods were 4 weeks with an additional week for withdrawal. The experimental diets included 0, 11, 22, 44 or 88 mg kg‐1 arsenic from roxarsone, respectively. Dietary arsenic above 44 mg kg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
21
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 10 publications
8
21
2
Order By: Relevance
“…However, the arsenic toxicity caused hepatic insufficiency and vitamin E and spirulina improved the hepatic functions (decreased SGOT compared to arsenic treated rats), which were supported the findings of Richmond (1986) and Romay et al (1999), who stated that spirulina reduced hepatic damage due to drug abuse and heavy metal exposure. Previous study in layer birds observed that the SGPT, SGOT, ALP and LDH were increased due to dietary arsenic (Chiou et al, 1997). Akter et al (2010) reported that serum activity of aspartate aminotransferase (AST) was increased by arsenic intoxication but serum creatinine values were fluctuating of goat.…”
Section: Discussionmentioning
confidence: 99%
“…However, the arsenic toxicity caused hepatic insufficiency and vitamin E and spirulina improved the hepatic functions (decreased SGOT compared to arsenic treated rats), which were supported the findings of Richmond (1986) and Romay et al (1999), who stated that spirulina reduced hepatic damage due to drug abuse and heavy metal exposure. Previous study in layer birds observed that the SGPT, SGOT, ALP and LDH were increased due to dietary arsenic (Chiou et al, 1997). Akter et al (2010) reported that serum activity of aspartate aminotransferase (AST) was increased by arsenic intoxication but serum creatinine values were fluctuating of goat.…”
Section: Discussionmentioning
confidence: 99%
“…At 40-50 mg roxarsone/kg feed, layers experience decreased egg production, feed intake, body weight gain, and liver weight gain (Chiou et al, 1997). At even higher doses (i.e., 300 mg/kg) layers ceased producing eggs, suffered liver damage, and experienced improper enzyme and hormonal functioning (Chiou et al, 1997;Wu et al, 2006). In all cases, increased arsenic concentrations were detected in the liver, eggs, and feces.…”
Section: Organoarsenical Sorption Onto Soilmentioning
confidence: 97%
“…Negative health impacts of the other organoarsenicals of concern have not been published; however, these effects are likely to be similar to those of roxarsone. Feeding of roxarsone (0-88 mg/kg) to layers over a period of 4-5 weeks leads to deposition of 24-60 ng/g arsenic in eggs (Chiou et al, 1997). At 40-50 mg roxarsone/kg feed, layers experience decreased egg production, feed intake, body weight gain, and liver weight gain (Chiou et al, 1997).…”
Section: Organoarsenical Sorption Onto Soilmentioning
confidence: 99%
See 2 more Smart Citations